BIMTEK PROMOSI BRANDING WONDERFUL INDONESIA: STRATEGI DIGITAL MARKETING PARIWISATA KEPULAUAN MERANTI - Sandi Fadilah; Yusriadi Yusriadi (Jurnal Pengabdian Kompetitif, 2026)
Meranti Islands Regency, Riau Province, has significant tourism potential; however, its digital promotion remains underdeveloped. This Community Service (PkM) program was conducted through a Technical Guidance (Bimtek) workshop entitled “Promoting the Wonderful Indonesia Brand Through Social Media,” organized by the Ministry of Tourism of the Republic of Indonesia in collaboration with the Youth, Sports, and Tourism Office of the Meranti Islands Regency on May 9, 2026. The program involved 75 participants, including tourism entrepreneurs, homestay managers, tour guides, souvenir artisans, culinary business owners, and local government representatives. The activities combined interactive lectures, live demonstrations, and hands-on workshops. The training covered digital tourism marketing strategies, effective use of social media platforms, smartphone-based content creation, social media analytics, and the development of a 30-day promotional action plan based on local tourism potential. Evaluation results indicated a 95% participant satisfaction rate and an 85% improvement in digital marketing knowledge. Participants also committed to consistently producing tourism promotional content, thereby strengthening destination branding and enhancing regional tourism competitiveness